2021
DOI: 10.1177/17579759211044079
|View full text |Cite
|
Sign up to set email alerts
|

From health education to digital health literacy – building on the past to shape the future

Abstract: Health education has continuously evolved and taken several distinctive forms over the decades. The emergence of new concepts such as health promotion and health literacy have helped to shape and refine our understanding of how the purpose, content and methods of health education can adapt with to new public health methods and priorities. Viewing health education through the lens of health literacy has been particularly helpful in differentiating between traditional task-focused health education, and skills-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Moreover, competencies still found that the inability to recognize valid health information or not was due to the assumption that the health information available on the internet had been checked by another party. namely 161 respondents [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, competencies still found that the inability to recognize valid health information or not was due to the assumption that the health information available on the internet had been checked by another party. namely 161 respondents [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Through health education, to influence the behavior of the elderly to achieve three-level prevention [ 39 ]. Health education can take various forms, such as lectures on widespread science knowledge, street publicity, face-to-face health education, health education prescriptions, and holding publicity boards [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that HL is a health determinant, mediator, and moderator, it is important to ensure that citizens access reliable, useful, and updated health information to help them make the best decisions about their personal health, their family’s health, and the community’s health [ 9 - 11 ]. Proper access to information allows to promote and increase citizen empowerment so that they participate in their health care, leading to shared responsibility and informed decision-making [ 12 ].…”
Section: Introductionmentioning
confidence: 99%